Proposing a Revised Pedestrian Walkway Level of Service Based on Characteristics of Pedestrian Interactive Behaviours in China - Xiaonian Shan; Jianhong Ye; Xiaohong Chen (Promet - Traffic&Transportation, 2016)
The objective of this study is to analyse characteristics of Pedestrian Interactive Behaviours (PIBs) in order to propose a revised pedestrian walkway Level of Service (LOS) in China. Field data on overtaking and evasive behaviours were collected at a metro station walkway in Shanghai, China to calculate macro and micro indicators. Occurrence intensities of these two PIBs initially increased with moderate density and later decreased with high density that reduced available space. PIBs were also analysed in terms of sideways behaviours to account for the varying difficulties of PIBs at different densities. It was found that available space for PIBs was the main factor contributing to the intensity features. Moreover, the different space demands of the two PIBs resulted in different features between them. Finally, a revised pedestrian walkway LOS was proposed based on the macro and micro characteristics of PIBs in China.